INTEGRAL ALGORITHM OF P300 RECOGNITION IN EEG FOR BCI APPLICATION - S N Agapov; V A Bulanov; A V Zakharov; M S Sergeeva; V F Pyatin (Наука и инновации в медицине, 2016)
Aim - developing the integral algorithm of recognition of the evoked potential (ERP-response) to a target visual stimulus and testing of the proposed algorithm on the wireless 5-channel electroencephalograph Emotiv Insight with “dry” electrodes. Materials and methods. The objects of the study were the EEG records of five volunteers. Were used 5-channel wireless EEG headset Emotiv Insight, self-developed software «eSpeller», software environment MathWork® MATLAB R2015a. Results. It was found that the proposed integral algorithm of recognition of electrical activity of the cerebral cortex to a target visual stimulus shows the accuracy of the detection from 71.5% to 90.6% with the average value 80.1+7.2%, using EEG headset Emotiv Insight. Conclusion. The algorithm shows a high level of reliability of recognition of evoked potential to a target visual stimulus, does not require large computing power, sophisticated classification methods and machine learning. The testing of the algorithm suggests the possibility of using the electroencephalograph Emotiv Insight with "dry" electrodes in the development of BCI.